Characteristics of mechanical metamaterials based on buckling elements. (May 2017) - Findeisen, Claudio; Hohe, Jörg; Kadic, Muamer; Gumbsch, Peter
Highlights: Metamaterials composed of unstable elements are studied on different length scales. (85) Energy dissipation relies on transformation of external work to vibrations. (77) Dissipation shows neither viscoelastic nor plastic characteristics. (69) Effective properties can be programmed within the same graded microstructure. (77) Programming is triggered by loading history only. (83) Abstract: Metamaterials are composed of structural elements and derive their properties mainly from the inner structure of the elements, rather than the properties of their constituent material. By designing an unstable structural element as the building block of a metamaterial, many interesting effective material properties can be obtained. The deformation and dissipation mechanisms of such a material built from unstable structural elements is studied in detail. To do so a combination of analytical, semi-analytical, and numerical models are applied to a single buckling element, a periodic cell, and finite size combinations of buckling elements including gradients in the properties of the building blocks. This not only provides insight into the micromechanics and the resulting effective behavior of such metamaterials, but also makes them accessible on the different relevant length scales. A metamaterial built from these building blocks shows programmable or switchable properties and can display energy dissipation with fully reversible deformation, distinguishing it from plastic materials, and timescale independent behavior, distinguishing it from viscoelastic materials.